Parameters of vibration imaging and psychophysiological reactions in highly qualified athletes specializing in bullet and bench shooting - Sturchak, I. S.; Abramova, T. F.; Nikitina, T. M.; Polfuntikova, A. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the information content of the innovative vibraimage technology (VibraMed10, 2020), taking into account the psychophysiological indicators of the state of athletes.